2009
DOI: 10.1021/nn800593m
|View full text |Cite
|
Sign up to set email alerts
|

Practical Chemical Sensors from Chemically Derived Graphene

Abstract: We report the development of useful chemical sensors from chemically converted graphene dispersions using spin coating to create single-layer films on interdigitated electrode arrays. Dispersions of graphene in anhydrous hydrazine are formed from graphite oxide. Preliminary results are presented on the detection of NO 2 , NH 3 , and 2,4-dinitrotoluene using this simple and scalable fabrication method for practical devices. Current versus voltage curves are linear and ohmic in all cases, studied independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
861
0
5

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,373 publications
(911 citation statements)
references
References 31 publications
27
861
0
5
Order By: Relevance
“…For example, gas sensors from a graphene-based FET can perform with high sensitivity and low noise. The detection mechanism is due to adsorbed molecules transferring charge to the graphene sheet and changing its resistivity [157][158][159] .…”
Section: Molecular Sensing Applicationsmentioning
confidence: 99%
“…For example, gas sensors from a graphene-based FET can perform with high sensitivity and low noise. The detection mechanism is due to adsorbed molecules transferring charge to the graphene sheet and changing its resistivity [157][158][159] .…”
Section: Molecular Sensing Applicationsmentioning
confidence: 99%
“…Thirdly, graphene has very few crystal defects, which could come up with noise by thermal minimum [45,46]. Finally, large-area ohmic contacts observed in graphene contribute to the reduction of resistance, resulting in making the measurements more convenient [44,47].…”
Section: Graphene Based Sensorsmentioning
confidence: 99%
“…1,2 For example, in a single layer of graphene electrons behave as massless Dirac fermions, resulting in potential applications for sensors, high mobility transistors, transparent conducting electrodes, and photocatalyst supports. [3][4][5] This has sparked much recent interest toward understanding how the bulk properties of other layered van der Waals bonded crystal structures (MoS2, WS2, Bi2Se3, BN, etc…) change when prepared as isolated individual sheets. 6,7 For example, bulk MoS2 normally has an indirect band gap at 1.29 eV, whereas isolated single layers of MoS2 have a direct gap (1.8 eV).…”
mentioning
confidence: 99%
“…13 Other Group IV layered lattices, may maintain appreciable conductivity when the atoms are in the sp 3 -hybridized state. Recently, single-layer thick sp 2 and sp 3 group IV systems have attracted considerable theoretical and experimental interest. [14][15][16][17] It has been previously shown that layered Zintl phases such as CaSi2 and CaGe2 can be topochemically deintercalated in aqueous HCl at low temperatures to produce layered silicon and germanium solids.…”
mentioning
confidence: 99%